Policy and programmatic changes resulting from the biennial reviews and agriculture joint sector reviews under the Comprehensive Africa Agriculture Development Programme (CAADP). Third Biennial Review Brief: Africa-Wide - Matchaya, Greenwell C.; Yade, M.; Guthiga, P.; Tefera, W.; Yamdjeu, A. W. (Regional Strategic Analysis and Knowledge Support System for Southern Africa / AKADEMIYA2063, 2021)
This brief analyzes selected policy and programmatic changes reported by countries across Africa resulting from the BRs and the agricultural JSRs. It is based on data and other information collected using an online questionnaire from the Directors of Agricultural Planning, or their representatives, from 14 countries—Angola, Burkina Faso, Chad, Ethiopia, Kenya, Malawi, Mali, Mozambique, Namibia, Rwanda, Senegal, Sierra Leone, and Zambia— and from representatives of two RECs, the East African Community and the Southern African Development Community. In addition, a review was conducted of the country BR briefs produced following the first BR of 2017 (AUC 2018) and the second of 2019 (AUC 2020) for several of these countries. The BR data reported by the countries was also analyzed.